A TDP‐43 proteinopathy mouse model of motor neuron disease. (December 2021) - Dopler, Matthew B; Gitcho, Michael A.; Cox, Keyshawn E
Abstract: Background: Motor neuron disease (MND) is characterized by both upper and lower motor neuron death. The average lifespan, after diagnosis, is ∼5 years, primarily due to respiratory failure and pneumonia with no effective treatment for the disease. Over 95% of all cases are pathologically characterized by cytoplasmic accumulation of hyperphosphorylated and ubiquitinated transactive response DNA binding protein 43 (TDP‐43). While in frontotemporal dementia (FTD), ∼50% have TDP‐43 pathology. The comorbidly seen in individuals with both FTD and MND has been shown to have an accelerated disease progression. We have developed an inducible aggressive mouse model that displays some of the behavioral and pathological features associated with MND and FTD‐MND. Method: A transgenic mouse containing three familial mutations in human TDP‐43 was developed with a tetracycline response element (tetO‐3X‐TDP‐43)(Cyagen). Double transgenic mice were generated by driving tetO‐3XTDP‐43 expression with the neurofilament heavy promoter expressing tetracycline‐controlled transactivator protein ( NEFH‐tTA) throughout the spinal cord and brain. Expression of the transgene was turned off (+DOX) until mice are weaned (P21). Mice were evaluated for motor an anxiety‐like behavior. Pathological evaluation included biochemical solubility fractionation, mitochondrial isolation, immunohistochemistry, and primary neuronal culture. Result: An age‐dependent decrease in motor function leading to paralysis was observed at 45‐60 days. This is associated with an increase in inflammation in mice expressing pathological TDP‐43. Biochemical fragmentation of TDP‐43 is seen in the spinal cord and brain. Conclusion: This aggressive model has the versatility to be used to drive expression in muscle, the hippocampus, and astrocytes to possibly help in our understanding of neurodegeneration in inclusion body myopathy, limbic predominant age‐related TDP‐43 encephalopathy (LATE), and other TDP‐43 proteinopathies. It is important to develop animal models that recapitulate human disease in order to develop viable targets for therapeutic intervention.